Catalytic removal of aqueous contaminants on N-doped graphitic biochars: Inherent roles of adsorption and nonradical mechanism - Zhu, S.; Huang, X.; Ma, F.; Wang, L.; Duan, Xiaoguang; Wang, Shaobin (American Chemical Society, 2018)
Green and low-cost catalysts are important for rapid mineralization of organic contaminants in powerful advanced oxidation processes (AOPs). In this study, we reported N-doped graphitic biochars (N-BCs) as low-cost and efficient catalysts for peroxydisulfate (PDS) activation and degradation of diverse organic pollutants in water treatment including Orange G, phenol, sulfamethoxazole and bisphenol A. The biochars derived from wetland plants at high annealing temperatures (>700 °C) presented highly graphitic nanosheets, large specific surface areas (SSAs), and rich doped nitrogen. In particular, N-BC derived at 900 °C (N-BC900) exhibited the highest degradation rate, which was 39-fold and 6.5-fold of that on N-BC400 and pristine biochar, respectively, and the N-BC900 surpassed most popular metal or nanocarbon catalysts. Different from the radical-based oxidation in N-BC400/PDS via the persistent free radicals (PFRs), singlet oxygen and nonradical pathways (surface-confined activated persulfate/carbon complexes) were discovered to dominate the oxidation processes in N-BC900/PDS. Moreover, the adsorption of organics was determined to be the rate-limiting step, revealing the active sites toward adsorption and catalysis. This study not only provides robust and cheap carbonaceous materials for environmental remediation, but also enables the first insight into the graphitic biochar-based nonradical catalysis.